2017
DOI: 10.1002/ijc.30652
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the GNMT-HectH9-PREX2 tripartite relationship in the pathogenesis of hepatocellular carcinoma

Abstract: The pathogenesis of hepatocellular carcinoma (HCC) involves many molecular pathways. Glycine N-methyltransferase (GNMT) is downregulated in almost all HCC and its gene knockout mice developed HCC with high penetrance. We identified PREX2, a novel PTEN inhibitor, as a GNMT-interacting protein. Such interaction enhanced degradation of PREX2 through an E3 ligase HectH9-mediated proteasomal ubiquitination pathway. Depletion of GNMT or HectH9 resulted in AKT activation in a PREX2 dependent manner and enhanced cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 44 publications
(68 reference statements)
1
36
0
Order By: Relevance
“…GNMT has been implicated in a variety of cancers. For example, it is down-regulated in almost all hepatocellular carcinoma (HCC) [ 35 ]; although abundantly expressed in the normal liver, GNMT expression is decreased in HCC tissues. GNMT deficiency is also associated with an inherited disorder of methionine metabolism [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…GNMT has been implicated in a variety of cancers. For example, it is down-regulated in almost all hepatocellular carcinoma (HCC) [ 35 ]; although abundantly expressed in the normal liver, GNMT expression is decreased in HCC tissues. GNMT deficiency is also associated with an inherited disorder of methionine metabolism [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we identified a novel PTEN inhibitor-PREX2 as another GNMT-interacting protein. We showed that such interaction enhanced degradation of PREX2 through an E3 ligase HectH9-mediated proteasomal ubiquitination pathway 11 . These studies implicate that GNMT is actively involved in maintaining normal liver function and further support the role of GNMT as a tumor suppressor gene in HCC.…”
Section: Introductionmentioning
confidence: 87%
“…Previously, our group reported that the expression of hepatic glycine n-methyltransferase (GNMT) was down-regulated in NAFLD and HCC [19,20].…”
Section: Glutamate-cysteine Ligase Catalytic Subunitmentioning
confidence: 99%